From blood to fruit: Transcosmogenerational modernities in Akha Worlds of the Upper Mekong. - Morton, Micah F. (Anthropology & Humanism, 2025)
In this article, I introduce the concept of "transcosmogenerationality" to emphasize the sustained and dynamic significance of Ancestral relationalities to particular Indigenous modernities. I draw on the case of certain Akha communities in Southeast Asia and southwest China who are channeling wealth from booms in cash crops, such as coffee, rubber, and tea, into the "ritual economy" bridging the parallel and mutually dependent worlds of Ancestors and descendants. These communities are further channeling their wealth into local and transregional efforts to sustain and vitalize their Ancestral Ways and cultivate a pan‐Akha identitarian movement. Their motivations are to ensure their Ancestors remain always living and thus close to and of moral significance for the living living, sustain their and their descendants' receipt of Ancestral geeqlanq or vital life‐giving energy, redistribute wealth, and promote the status of their families and clans. I emphasize that growing wealth and access to consumer goods among Akha has led not to the decline, but rather, an intensification of Ancestral relationalities, which they view as the very source of this wealth. I further argue that Akha rites of transcosmogenerational commensality are especially concrete and revealing of the co‐presence and conviviality between and among Ancestors, Elders, and descendants.